Exercise Training Decreases Hepatic Injury and Metastases Through Changes in Immune Response to Liver Ischemia/Reperfusion in Mice. Issue 6 (16th March 2021) - Yazdani, Hamza O.; Kaltenmeier, Christof; Morder, Kristin; Moon, Juik; Traczek, Madelyn; Loughran, Patricia; Zamora, Ruben; Vodovotz, Yoram; Li, Feng; Wang, James H‐C.; Geller, David A.; Simmons, Richard L.; et al.
Abstract : Background and Aims: Liver ischemia/reperfusion injury (IRI) induces local and systemic inflammation in which neutrophil extracellular traps (NETs) are major drivers. IRI markedly augments metastatic growth, which is consistent with the notion that the liver IRI can serve as a premetastatic niche. Exercise training (ExT) confers a sustainable protection, reducing IRI in some animal models, and has been associated with improved survival in patients with cancer; however, the impact of ExT on liver IRI or development of hepatic metastases is unknown. Approach and Results: Mice were randomized into exercise (ExT) and sedentary groups before liver IRI and tumor injection. Computerized dynamic network analysis of 20 inflammatory mediators was used to dissect the sequence of mediator interactions after ischemia/reperfusion (I/R) that induce injury. ExT mice showed a significant decrease in hepatic IRI and tissue necrosis. This coincided with disassembly of complex networks among inflammatory mediators seen in sedentary mice. Neutrophil infiltration and NET formation were decreased in the ExT group, which suppressed the expression of liver endothelial cell adhesion molecules. Concurrently, ExT mice revealed a distinct population of infiltrating macrophages expressing M2 phenotypic genes. In a metastatic model, fewer metastases were present 3 weeks after I/R in the ExT mice, a finding that correlated with a marked increase in tumor‐suppressing T cells within the tumor microenvironment. Conclusions: ExT preconditioning mitigates the inflammatory response to liver IRI, protecting the liver from injury and metastases. In light of these findings, potential may exist for the reduction of liver premetastatic niches induced by liver IRI through the use of ExT as a nonpharmacologic therapy before curative surgical approaches.